2015
DOI: 10.1053/j.gastro.2014.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers Identify Subtypes of Stage III Colon Cancer Associated With Patient Outcomes

Abstract: Background & Aims Categorization of colon cancers into distinct subtypes using a combination of pathway-based biomarkers could provide insight into stage-independent variability in outcomes. Methods We used a PCR-based assay to detect mutations in BRAF (V600E) and in KRAS in 2720 stage III cancer samples, collected prospectively from patients participating in an adjuvant chemotherapy trial (NCCTG N0147). Tumors deficient or proficient in DNA mismatch repair (MMR) were identified based on detection of MLH1, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
282
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 291 publications
(301 citation statements)
references
References 52 publications
17
282
2
Order By: Relevance
“…In prospectively col- (Andre et al, 2015;Gavin et al, 2013;Guastadisegni et al, 2010;Klingbiel et al, 2015;Popat et al, 2005;Roth et al, 2012;Sinicrope et al, 2015). lected tumor tissue MSI was detected in 314 of 2580 stage-III CRCs and was prognostic overall for time to relapse (TTR), but not for DFS or OS (Sinicrope et al, 2013a).…”
Section: Msi As a Biomarker With Cetuximab Adjuvant Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In prospectively col- (Andre et al, 2015;Gavin et al, 2013;Guastadisegni et al, 2010;Klingbiel et al, 2015;Popat et al, 2005;Roth et al, 2012;Sinicrope et al, 2015). lected tumor tissue MSI was detected in 314 of 2580 stage-III CRCs and was prognostic overall for time to relapse (TTR), but not for DFS or OS (Sinicrope et al, 2013a).…”
Section: Msi As a Biomarker With Cetuximab Adjuvant Therapymentioning
confidence: 99%
“…2. Prognosis -Several studies have shown dMMR CRC has a better prognosis than MMR proficient (pMMR) CRC Guastadisegni et al, 2010;Klingbiel et al, 2015;Popat et al, 2005;Roth et al, 2010;Sinicrope et al, 2015). MSI tumours are less prone to lymph node (Mohan et al, 2016) and synchronous liver metastasis (Nordholm-Carstensen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the patients are mostly women above 70 years of age with tumours located in the proximal part of the colon. Here mucinous and poorly differentiated cancers are dominating with metastases mostly to the lymph nodes and more rarely to the lungs [36,37]. The BRAF mutation indicates an adverse course of the disease [38], yet its prediction significance still remains an issue that requires some further research [34].…”
Section: Braf Gene Mutation (Iia)mentioning
confidence: 99%
“…The difference between the proximal and distal localization is also confi rmed with genomic profi les: the majority of proximal serrated polyps developed after BRAF mutations, they are CIN-negative with high levels of MSI and CIMP. The majority of distal tumours develop after a KRAS mutation, they are CIN-positive with low levels of MSI and CIMP [23].…”
Section: Classifi Cation Of Serrated Polypsmentioning
confidence: 99%